Explorative analysis of the short- and longer-term effects of economic conditions at labor market entry on leaving the parental home and family formation - Christian König; Thomas Biegert; Jan Paul Heisig; Heike Solga (INVEST Research Flagship Centre / University of Turku, 2025)
This report examines the lasting spillover effects of labor market conditions at entry on union formation (marriage/cohabitation), leaving the parental home (becoming independent) and fertility. Using EU-LFS data, we analyze entry cohorts from 2001 to 2011 from 103 European regions (NUTS1). We focus on regions because they are closer to individuals' actual labor markets than the national level. We also explore the moderating role of family-related contextual factors at the macro level (e.g., family policies, childcare infrastructure, and gender employment attitudes) that may influence the costs of parenthood.
Keywords: 330